Integrated Healthcare Saving Technologies Innovative Potential in Higher Education Institutions - Diachenko-Bohun, Maryna; Rybalko, Lina; Hryniova, Maryna; Moroz, Yury (International Journal of Engineering and Technology, 2018)
The article analyzes the innovative potential, the essence of which is orientation of the educational process on the potential human rights and their implementation, and also describes the tasks and circumstances of the use of integrated healthcare saving technologies in higher education institutions. Particular attention is paid to the fact that an innovative approach to student learning should be systematic and cover all aspects of educational work in the preparation of future specialists, with the need to review the theoretical and practical approaches to the content of education, vocational teacher training, development of new technologies and teaching methods. At the same time, the main objective of innovative educational technologies is to prepare a student for life in an ever-changing world. Thus, the teacher can act as a participant, developer, researcher, user and advocate of new pedagogical technologies, theories and concepts.Â